Análisis del Sistema Administrativo Safdwin de la Empresa Wineswin S.A. de la Ciudad de Babahoyo. - Palacios Ortega, Ruth Del Rocío (2018)
Wineswim S.A. Formerly also known as Distribuidora Babahoyo in which there were three shareholders who were the two children and their father (Oñate Family); is a company that sells construction materials in large and small quantities are these: sand, gravel, cement, belts, electrical materials, iron, belts, pipes in general, water cisterns, plumbing materials: pipes pvc, showers, hand keys, sinks, toilets, ceramics, etc. He has been working in the market under the name of Wineswin S.A. since April 4, 2006 when he joined the Disensa franchise, currently owning Mr. and Mrs. Oñate and Néstor Oñate as owners. Since all this lapse of time, its popularity has been receiving great acceptance with the people of the city who come daily to this business to try to acquire the materials they need because as we know, construction is a business that is done daily and needs the acquisition of materials to increase their works, as well as increasing sales the company was forced to make the acquisition of a system that allows and facilitates the performance of daily tasks that occur in these facilities. Because as we know that insecurity has increased enormously making it practically impossible for a business to have its information and the detail of its paper accounts, this is not only at the social level but also at the computer level, so it is necessary that Every company has a fast and efficient computer system so that it does not hinder the activities of the user and the client that requires to request some information that is found in said system.